Ibn 'Arabi on Human Freedom, Destiny and the Problem of Evil - Diyab, Adib Nayif (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Ibn 'Arabi on Human Freedom, Destiny and the Problem of Evil